Electrical Losses in Primary Distribution Networks: Case in Holguin Province - Alvaro Laurencio Pérez; Igor R. Pérez Maliuk; Olga Pérez Maliuk (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2023)
The electrical losses constitute an indicator of the technical state of the electrical networks, which can reach up to 70% of the total losses that occur in an electrical circuit. In this work, the calculation of the technical losses in 140 electrical distribution networks was carried out in the school belonging to the Holguín province in Cuba. The statistical calculation is performed in order to understand the electrical losses in primary distribution networks of the Holguín province. The method used by Empresa Eléctrica Holguín was acquired for power losses, which considered the number of customers, the maximum demand, and the length belonging to the circuit under study. The Buller equation was used to calculate energy losses, which relates the load and loss factors utilizing a coefficient obtained by statistical considerations. The most affected municipalities were Sagua de Tánamo, Calixto García, and Cacocún, whose losses represented 45% of the total losses. On the other hand, the characteristic coefficient for local primary distribution networks was 0.27.